2018
DOI: 10.1007/s00270-018-1930-3
|View full text |Cite
|
Sign up to set email alerts
|

Image Fusion Guidance with Pre-procedural CT with Real-Time Fluoroscopy for Adrenal Venous Sampling

Abstract: Although the contribution to improving the technical success rates was small in our study, IF can effectively reduce procedure time, radiation exposure, and volume of contrast medium during AVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…[20,21] The first of these is associated with an increased radiation dose, and both are costlier than the conventional catheterization technique described here. The median DAP during AVS in the study was 11.3 Gy.cm 2 , which is lower than previously published reports ranging between 32.5 Gy.cm 2 and 72.2 Gy.cm 2 [8][9][10][11] including on some new generation angiography machines. Some of the differences may be, as some groups use CBCT to improve the success rate at the expense of an increased dose.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…[20,21] The first of these is associated with an increased radiation dose, and both are costlier than the conventional catheterization technique described here. The median DAP during AVS in the study was 11.3 Gy.cm 2 , which is lower than previously published reports ranging between 32.5 Gy.cm 2 and 72.2 Gy.cm 2 [8][9][10][11] including on some new generation angiography machines. Some of the differences may be, as some groups use CBCT to improve the success rate at the expense of an increased dose.…”
Section: Discussioncontrasting
confidence: 73%
“…Intraprocedural image fusion of prior CT data with live fluoroscopic images has been shown to aid right adrenal vein catheterization and to reduce both fluoroscopy time and radiation exposure. [10] The authors of this article have shown a relative reduction in their radiation use, but the technique is still associated with a significant radiation dose and a prolonged procedure time. It may be a useful technique to help inexperienced operators improve right adrenal vein catheterization during initial procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol was repeated until venous access was achieved. Subsequently, AVS was performed according to the method described in previous reports [21,23,24]. The access site was checked after 2 h of bed rest and the next day to evaluate hematoma.…”
Section: Venous Access Methodsmentioning
confidence: 99%
“…Only few approaches for improvement of adrenal vein sampling combine preand peri-interventional methods such as the simple to use planning ruler approach successfully evaluated in our study. Technically more demanding approaches have been described by Morita et al or Busser et al who propose co-registration of pre-interventionally acquired CTs and real-time fluoroscopy during adrenal vein sampling [21,35]. In the study by Morita et al, the proposed co-registration technique significantly reduced fluoroscopy time (95.6 vs. 108.4 min), DAP (43.1 vs 72.2 Gy � cm 2 ) and contrast volume (54.6 vs 65.7 ml) [35].…”
Section: Plos Onementioning
confidence: 99%